NURSING ASSISTANCE TO CHILDREN WITH DIABETES MELLITUS - Silva Sousa, Natalia; Silva Oliveira, Geane; Caroline de Souza, Anne; Sybelly Silva Matos, Gyanna; Rolim de Oliveira, Rafaela; Lívia Silva Fonseca Moreira de Medeiros, Renata (Health and Society, 2022)
Introduction: Diabetes Mellitus is defined as a non-communicable chronic disease, characterized by hyperglycemia and associated complications, resulting from the lack of insulin and/or the inability of insulin to properly exert its effects on the body, which can cause several health risks, such as dysfunction and failure of various organs. Objective: Evidence through the literature, which nursing care for children with diabetes mellitus. Methodology: This is an integrative review, where the search was carried out through the scientific databases: SCIELO, LILACS and BDENF, using the inclusion criteria freely available in Portuguese published in the last 5 years. Results and Discussions: Through literature analysis, some important points about nursing care for children with diabetes mellitus were highlighted. Based on this, initially it is important to consider that the care team is the one that most lives with children with diabetes, in this sense, it is essential to care for and develop health education actions, aimed at guidelines about the chronic disease as well as the importance of adherence to the treatment. Conclusion: Thus, carrying out this study, it can be seen that the main care that should be provided to children with diabetes mellitus is health education, aimed not only at the patient, but also at their caregivers and family members. Nursing care goes beyond monitoring and is essential to provide the necessary support to the patient.